Mapping discourses on mosque education in the Netherlands: a content analysis of the Dutch press, 2010–2016. Issue 3 (4th May 2019) - Sözeri, Semiha; Kosar-Altinyelken, Hülya; Volman, Monique
ABSTRACT: This article provides an overview of the discourses on Dutch mosque education. Based on a review of the scholarly debates on mosque education in West, we conducted a qualitative content analysis of newspaper articles containing references to mosque education between 2010 and 2016 ( N  = 45). The data are sampled from the five largest Dutch newspapers. Most of the themes emerging from the literature are also reflected in the discourses on mosque education in the press. In line with other media analysis on representation of Muslims, the portrayal of mosque education in the Dutch press is also mainly negative. The key issues in the press portrayals included use of corporal punishment, inadequate training of imams, reinforcement of conservative gender norms, intensification of social segregation, links with religious extremism and local opposition to mosques. Fewer references concern the positive influence of mosque education on cognitive skills and identity development of the Muslim children.